2011
DOI: 10.1037/a0023650
|View full text |Cite
|
Sign up to set email alerts
|

Coping with client death: Using a case study to discuss the effects of accidental, undetermined, and suicidal deaths on therapists.

Abstract: Over one-quarter of psychologists and psychiatrists will lose a client to suicide, and the impact of suicide on therapists is profound. Therapists report both personal (e.g., emotional) and professional (e.g., fears of litigation, doubts about competency) reactions to client suicide, and these reactions are thought to be pronounced for therapists-in-training. However, little is known about the effect of nonsuicidal client deaths on therapists, especially how the experience of a client suicide might compare wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 47 publications
(121 reference statements)
2
32
0
Order By: Relevance
“…This challenge often spurred personal and professional growth for geropsychologists as they adapted and developed strategies to cope with their experiences. Thus, the present results supported prior findings that client death led to growth and professional development for clinicians (Veilleux, 2011;O'Brien, 2011;Lardaro, 1988). Further, specific coping strategies identified by this study such as cognitive reframing of client death and using rituals to gain a sense of closure demonstrate specific ways that professionals cope with this phenomenon.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This challenge often spurred personal and professional growth for geropsychologists as they adapted and developed strategies to cope with their experiences. Thus, the present results supported prior findings that client death led to growth and professional development for clinicians (Veilleux, 2011;O'Brien, 2011;Lardaro, 1988). Further, specific coping strategies identified by this study such as cognitive reframing of client death and using rituals to gain a sense of closure demonstrate specific ways that professionals cope with this phenomenon.…”
Section: Discussionsupporting
confidence: 91%
“…Existing research has relied on case studies and clinical case reflections based largely on the experiences of generalist practitioners who experienced client death as a rare and unexpected event. Results of these studies identified some common issues therapists experience when a client dies: countertransference effects in which experiences from their personal histories complicated their reactions, struggle with the ambiguity of the therapeutic relationship, and feelings of guilt, denial, and avoidance (O'Brien, 2011;Veilleux, 2011;Rubel, 2004;Schwartz, 2004;Lardaro, 1988).…”
Section: The Impact Of Client Death On Clinical Geropsychologistsmentioning
confidence: 99%
“…Differences between such responses to patients’ suicide deaths, attempts of different severity, and unexpected non-suicide deaths have not been studied and are poorly understood [33]. It is possible that the differences in recalled reaction to patients in the encounters preceding such events are attributable to their recollection being colored differently by those very events.…”
Section: Discussionmentioning
confidence: 99%
“…When a mental health professional sees a patient who is at risk for suicide, he or she is faced with the need to make decisions about patient care that can have serious life‐or‐death consequences. If a patient dies by suicide, there is a significant emotional impact on the patient’s family, his or her social network, and the clinician or clinician‐in‐training treating the patient (Calhoun, Selby, & Faulstich, 1980; Cerel, Roberts, & Nilsen, 2005; Chemtob, Hamada, Bauer, Torigoe, & Kinney, 1988b; Kleespies, Penk, & Forsyth, 1993; Veilleux, 2011). When a patient of a mental health professional dies by suicide, clinical, ethical, and legal questions may arise about the adequacy of the clinician’s evaluation and about the sufficiency of his or her training to perform such evaluations.…”
Section: Introductionmentioning
confidence: 99%